PENGARUH LINGKUNGAN KERJA DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI DEPOT ARSIP PADA DINAS PERPUSTAKAAN DAN KEARSIPAN KOTA TANGERANG SELATAN - Muchlisin, Dwiyan; Indirasari, Indri (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2025)
This study aims to examine the influence of Work Environment (X1) and Work Discipline (X2) on Employee Performance, both partially and simultaneously, at the Archive Depot of the Library and Archives Office of South Tangerang City. The method used is a quantitative approach with multiple linear regression analysis. The results show that partially, the Work Environment has a positive and significant effect on Employee Performance, with a t-value of 5.294 > t-table 2.021 and a p-value of 0.001 < 0.05. Work Discipline also has a significant effect, with a t-value of 5.339 > t-table 2.021 and a p-value of 0.001 < 0.05. Simultaneously, both variables significantly affect performance, with an F-value of 27.081 > F-table 3,195 and a p-value of 0.001 < 0.05. The resulting regression equation is Y = 1.105 + 0.393X1 + 0.335X2. The limitations of this study include difficulties in obtaining supporting data, obstacles in distributing questionnaires during working hours, and potential bias in respondents' survey answers. Keywords: Discipline, Employee, Performance